Healthcare providers’ perceptions of changes in guidelines for care of minors with gender dysphoria in Sweden: An interview study - Elsa Svantesson; Ida Linander (PLoS ONE, 2025)
Background The number of youths seeking care for gender dysphoria has increased globally over the last ten years. In December 2022, the Swedish National Board of Health and Welfare published an updated knowledge support for the care of minors (children and adolescents) with gender dysphoria. This knowledge support recommends stricter criteria for prescribing puberty blockers and cross-gender hormones to minors, and differs both from previous healthcare practices and from international guidelines. Aim This study aimed to explore healthcare professionals’ perceptions of the updated knowledge support and its impact on healthcare practices and the care seekers (minors with gender dysphoria). Methods This qualitative interview study included 11 participants who worked clinically with gender-affirming care of minors (both evaluation and providing medical interventions). The participants came from different regions, different evaluation teams, and different professions. Reflexive thematic analysis was used. Results While the new knowledge support was partly intended to solve geographical differences, different evaluation teams had implemented the new guidelines differently. New criteria around childhood debut, neuropsychiatric conditions, and hormonal treatment seemed to have partly changed the conditions for the evaluation. The greatest change had been regarding access to puberty blockers and hormonal treatment. Some participants argued for a larger shift towards psychosocial support, while others highlighted the tension between care seekers’ needs and the shrinking opportunities to help based on the new guidelines. Some participants perceived that people lacking in expert knowledge had affected the content of the knowledge support. Conclusions Differing opinions of the knowledge support were expressed by healthcare providers working with gender-affirming care for minors. Some were pleased with the new guidelines and believed the new knowledge support to be clearer than the old one. Others were more critical, stating that the knowledge support had not taken clinical experience into consideration, was too open to interpretation, and was too restrictive.